UPAYA MENINGKATKAN HASIL BELAJAR SISWA DALAM MATA PELAJARAN SOSIOLOGI MELALUI MODEL PEMBELAJARAN COOPERATIVE SCRIPT PADA SISWA KELAS X IPS.4 SMA N 1 PASAMAN - Mairoza Mairoza (JURNAL MANAJEMEN PENDIDIKAN, 2017)
Based on the results of Class X student learning IPS.4 SMA N 1 Pasaman in the subjects of Sociology found that results for students in the subjects of Sociology is still very low. The average student learning outcomes are still under KKM. The purpose of this study is to describe and obtain information about efforts to improve student learning outcomes in subjects Sociology sub Mendeskripiskan values and norms in society through Learning Model Cooperative Script in class X SMA N 1 Pasaman IPS.4 West Pasaman.This research is a class act. The procedure in this research include planning, action, observation and reflection. The study consisted of two cycles of the four meetings. Subjects consisted of 32 learners IPS.4 Class X SMAN 1 Pasaman. Data were collected by using observation sheet and daily tests. Data were analyzed using percentages.Based on the results of research and discussion that has been raised, it can be concluded that the Cooperative Learning Model SCRIPT can improve student learning outcomes in subjects Sociology sub Mendeskripiskan values and norms in masyarakatdi SMA N 1 Pasaman. Learning outcomes of students from the first cycle to the second cycle. The results of students in the first cycle was 48.41 (less) increased to 84.53 (Good) with an increase of 36.12%.